Estudo de sabões de óleos vegetais como inibidores de corrosão em fluido salino - Santana, Tamires Silva de (2018)
Carbon steel is one of the most used materials in the oil industry. Present in the manufacturing of the exploration, production, transportation and storage sectors, is characterized by low resistance to corrosion and the deterioration of these pipelines by electrochemical corrosion, which is one of the biggest problems in the industry. The demands for corrosion inhibitors promote several studies to obtain and evaluate chemical compounds with the capacity to retard or inhibit corrosion reactions. To avoid the impact of compounds with high toxicity, several studies have been dedicated to the use of environmentally friendly products. In the present work, the efficacy of 4 surfactants obtained through saponification of vegetable oils: castor bean, coconut, soybean and sunflower was evaluated as corrosion inhibitors to carbon steel API5LX Gr X42 for medium containing 3.5% NaCl. The surfactant solutions were characterized and studied using the techniques of: (i) light scattering to obtain particle size / droplet; (ii) goniometry for contact angle measurement and (iii) surface tension to obtain critical micelle concentration. The electrochemical parameters were calculated from the polarization curves that generated knowledge of the kinetics of the anodic and cathodic reactions. The corrosion inhibition efficiencies were calculated from the values of corrosion current density obtained by Tafel extrapolation methodology. The soaps stood out as good corrosion inhibitors, as they presented efficiency values above 70%. At high concentrations, the OMS had a maximum efficiency of 93.6% and this was due to its easy solubilization in saline medium, which enabled the calculation of the cmc (in the order of 10-2 mol / L), the measurement of the diameters of micelles (between 200 and 250 nm) and obtaining low contact angles (36.1º static, and 20.4º dynamic). At low concentrations, the surfactants that presented low solubility at the salt media, showed higher efficiencies, especially OSS at 10-6 mol / L, which presented an efficiency of 58.9%. These results demonstrate the economic viability of these surfactants, since they present low cost of obtaining and satisfactory efficiencies, even in low concentrations. The isotherm model that best suited the OMS adsorption (better polarization results) was Frumkin’ isotherm, with R2 of 0.94. The adsorption coefficient was on the order of 109 , showing high adsorptive ability and adsorption free energy of -64 KJ/mol, which represents a spontaneous chemisorising process. Positive interaction parameter, characterized the lateral attraction between the molecules of surfactant.